Design and Build A Prototype Internet of Things Based On Cooking Oil Distribution at PT. Lion Super Indo Jatibening - Steven Steven; Azpha Thoriq Mulyadi; Resha Wisnu Murti; Anggi Oktaviani; Dahlia Sarkawi; Deny Novianti (Jurnal Riset Informatika, 2022)
The scarcity of cooking oil is the main factor for PT LION Superindo Jatibening to make provisions for limiting the purchase of cooking oil. Of course, some people use this to commit fraud in purchasing, namely, buying cooking oil beyond the predetermined limit by repurchasing it after a few hours from the previous purchase. Of course, some use this to cheat on purchasing cooking oil over the predetermined limits of repurchase within a few hours of previous purchases. Thus, the governmental tribunician is disproportionate to other customers, so many are not getting cooking oil and using RFID (radio identification) technology to create an automated system as an authentication medium and security system. The system is a card reading that contains the user or item data. This technology assists in limiting purchases to greater efficiency, safety, and protection of people against the repurchasing of cooking oil. Fry oil distribution systems use IoT devices by applying PHP programming language based on websites that can be accessed and integrated with MySQL databases as data storage. For IoT devices, the primary device uses NodeMCU esp8266 as a microcontroller and rc522 RFID reader as modules to read an RFID card configured using microcontroller software.